Bounded renormalization with continuous penalization for level set interface capturing methods - Battaglia, Laura (2010)
In this work, a reinitialization procedure oriented to regularize the level set (LS) function field is presented. In LS approximations for two-fluid flow simulations, a scalar function indicates the presence of one or another phase and the interface between them. In general, the advection of such function produces a degradation of some properties of the LS function, such as the smoothness of the transition between phases and the correct position of the interface. The methodology introduced here, denominated bounded renormalization with continuous penalization, consists of solving by the finite element method a partial differential equation with certain distinguishing properties with the aim of keeping the desirable properties of the LS function. The performance of the strategy is evaluated for several typical cases in one, two and three-dimensional domains, for both the advection and the renormalization stages.